If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + m = 19 + -2m Solving 10 + m = 19 + -2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '2m' to each side of the equation. 10 + m + 2m = 19 + -2m + 2m Combine like terms: m + 2m = 3m 10 + 3m = 19 + -2m + 2m Combine like terms: -2m + 2m = 0 10 + 3m = 19 + 0 10 + 3m = 19 Add '-10' to each side of the equation. 10 + -10 + 3m = 19 + -10 Combine like terms: 10 + -10 = 0 0 + 3m = 19 + -10 3m = 19 + -10 Combine like terms: 19 + -10 = 9 3m = 9 Divide each side by '3'. m = 3 Simplifying m = 3
| m^3+27n^3=0 | | X^2+8=-9 | | 3(x-2)-18=0 | | x+3+2x-2=128 | | -4+5=-5 | | 2x+2=6x+4 | | -15y=-195 | | 20+x=5 | | 7x-13=24 | | -7=x+8 | | d-1=-23 | | 11z=-88 | | -5x=-5 | | 4x-7=x+5 | | 2t^2-8t-15=0 | | 9x-8=12x+3 | | 8x-(6x+5)=3x-33 | | -3d+8+6d=-13 | | 20x^2+7x-15=0 | | x^2+6y-5z+k=75y-3k+x^3-z | | 2x^2-5x-33=0 | | 3xn=23.4 | | -16t^2+75t=0 | | 7x-7=7x-7 | | 5z-4z+13=11 | | 6x^3-10x^2y-56xy^2=0 | | (x+0)*(x-70)=0 | | 3x^2+2xy-8y^2=0 | | 4m+8m-140=0 | | 2x^2-11xy+5y^2=0 | | 6z+7=0 | | 6n-39=-3 |